Strategi Peningkatan Kesadaran PBB Melalui Mobil Keliling Bapenda UPTB 3 Sawahan, Surabaya - Naurah, Adinda Putri; Imaningsih, Niniek; Fadil, Cholid (Yumary: Jurnal Pengabdian kepada Masyarakat, 2025)
Purpose: This research explores the effectiveness of the mobile car program initiated by the Regional Revenue Agency (Bapenda) UPTB 3 Surabaya City to increase public awareness of Land and Building Tax (PBB). Methodology: This research is a qualitative study with a descriptive design, which is a benchmark for participation in the effectiveness of PBB voting. This study describes the role and strategies of the PBB mobile car. Results: According to several sources, the PBB mobile car program in Sawahan District, Surabaya received a positive response from the community. Increased insight into taxation and simplification of the administrative process.  The main strategy for mobile cars is to choose strategic places, such as markets and public places, with a regular schedule with friendly and communicative officers. Conclusion: The mobile car program in Sawahan District, Surabaya, significantly increased public awareness of PBB. The public is easier to reach, educated with clearer information, and makes the tax payment process easier for the government. This program received positive responses from both taxpayers and related officers, although challenges in expanding public reach and understanding remain. Limitation: This study was conducted only at Bapenda UPTB 3, Sawahan District, Surabaya. Contribution: This research can increase public awareness, especially in Sawahan District, Surabaya, regarding the payment of PBB and as an evaluation material for Bapenda UPTB 3, Surabaya City Government to improve services in the field of PBB Payments to increase income and manage regional development.